صحیح مسلم اور صحیح بخاری کی افضلیت سے متعلق علمی آراء کا تقابلی جائزہ: A Comparative & Analytical Study of Scholarly Opinions on the Superiority of Sahih Muslim & Sahih al-Bukhari - Abdul Mannan; Dr. Khalid Zafarullah; Dr. Khalid Mahmood Arif (Al-Amīr Research Journal for Islamic Studies, 2025)
This research provides a comparative analysis of scholarly opinions regarding the relative superiority of Sahih al-Bukhari and Sahih Muslim, the two most authentic hadith collections after the Qur’an. The study identifies three principal viewpoints among scholars: (i) Sahih al-Bukhari is superior, (ii) Sahih Muslim is superior, and (iii) both are equal in authenticity. It presents detailed evidences supporting each stance, drawing from the works of prominent hadith scholars such as Ibn al-Salah, al-Nawawi, Ibn Kathir, Ibn Hajar al-Asqalani and al-Suyuti. The research concludes that Sahih al-Bukhari holds precedence in authenticity and methodological rigor due to its stricter conditions for narrators, higher standards of isnad (chain verification) and comprehensive jurisprudential insights reflected in its chapter headings. Meanwhile, Sahih Muslim excels in literary coherence, structural organization and ease of comprehension through the compilation of all variants of a narration in one place. Despite Sahih Muslim’s stylistic strengths, the consensus of the majority of classical scholars regards Sahih al-Bukhari as the most authentic book after the Qur’an, while Sahih Muslim remains an indispensable complement in the preservation of the Prophetic Sunnah. Keywords: Sahih al-Bukhari, Sahih Muslim, Hadith authenticity, comparative analysis, Islamic scholarship